OBESITAS DAN TINGKAT STRES BERHUBUNGAN DENGAN HIPERTENSI PADA ORANG DEWASA DI KELURAHAN KLAMPIS NGASEM, SURABAYA Obesity and Stress Level are Associated with Hypertension among Adulthood in Klampis Ngasem, Surabaya - Shirley Priscilla Gunawan; Merryana Adriana (Universitas Airlangga, 2020)
Globalization era has led to higher demands and expectancy for life, causing higher stress level followed by higher prevalence of obesity and hypertension. Obesity and stress has became risk factors of hypertension and heart disease. This study purposed for analyzing the correlation between obesity and stress level with hypertension among church community in Indonesian Christian Church (GKI) Manyar Surabaya. This study was an analytic observational study with a cross-sectional design. Subject of this study were chosen using simple random sampling method. Data were collected by interviewing subjects, calculating subjects’ Body Mass Index (BMI) based on their height and body weight measurement, measuring blood pressure and fi lling DASS-42 questionnaire. All data were analyzed with Spearman test using SPSS v25.0. 76 subjects aged 18-45 year were participated in this study. This study showed 21.1% subjects were overweight and 42.1% were obese. 65.8% subjects experienced stress with a DASS score above 14. Twenty seven subjects experienced prehypertension and 12 others experienced hypertension stage 1. Based on statistical calculation, obesity (r=0.577; p<0.001) and stress level (r=0.370; p=0.001) are positively correlated to hypertension. Health promotion should be held to increase knowledge and awareness about the danger of obesity and stress to hypertension. Therefore, people can put more eff orts to maintain ideal body weight, learn to manage stress well and control blood pressure regularly